2019
DOI: 10.1176/appi.neuropsych.18080195
|View full text |Cite
|
Sign up to set email alerts
|

Association of COMT Val158Met Polymorphism With Delirium Risk and Outcomes After Traumatic Brain Injury

Abstract: The authors investigated the association of the catechol-O-methyltransferase (COMT) gene Val 158 Met polymorphism with delirium risk and functional and cognitive outcomes among patients with complicated mild to moderate traumatic brain injury (TBI). Methods:In a prospective observational cohort study, patients were monitored for occurrence of delirium during the first 4 days of admission by using the Confusion Assessment Method. Functional and cognitive outcomes were evaluated with the Glasgow Outcome on Disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Reasons for exclusion were no diagnosis by physician or research personnel (428 studies), no characterization of predisposing or precipitating factors (338 studies), retrospective study design (86 studies), not diagnosed by reference standard (108 studies), no multivariable model (43 studies), delirium assessment not conducted in person (25 studies), not cohort or case-control design (20 studies), sample included less than 50 patients (12 studies), abstract only (18 studies), cohort previously reported (3 studies), and pediatric population (1 studies). Ultimately, 315 studies…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reasons for exclusion were no diagnosis by physician or research personnel (428 studies), no characterization of predisposing or precipitating factors (338 studies), retrospective study design (86 studies), not diagnosed by reference standard (108 studies), no multivariable model (43 studies), delirium assessment not conducted in person (25 studies), not cohort or case-control design (20 studies), sample included less than 50 patients (12 studies), abstract only (18 studies), cohort previously reported (3 studies), and pediatric population (1 studies). Ultimately, 315 studies…”
Section: Resultsmentioning
confidence: 99%
“…Delirium was measured by research personnel in 171 studies (54.3%), a combination of research personnel and physicians in 5 studies (1.6%), and a physician in 139 studies …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible this study was underpowered to find a weak association. Analysis of the COMT Val 158 Met polymorphism and its association with delirium would be useful to extend this work as this has previously been associated with delirium after head injury 23 although it has been reported to have no association with dementia in PD 24 .…”
Section: Discussionmentioning
confidence: 99%